AGE AND EDUCATION FACTORS TO CHOICE CONTRACEPTIVE WITH ATTITUDES ACCEPTORS ABOUT SIDE EFFECTS OF IMPLANTS - Nur Azizah; Wiwik Muhidayati; Diyan Wahyuningsih; Yuli Admasari; Wiwik Utami (Indonesian Midwifery and Health Sciences Journal, 2023)
Family planning is an attempt to measure the number of children and the desired birth spacing of children. The Government of Indonesia then launched a program or method to prevent and delay pregnancy. Acceptors' attitudes about side effects were related to factors consisting of age, education and parity. The purpose of this study was to determine the relationship between contraceptive selection factors and attitudes of family planning acceptors at the Sifa Husada Nganjuk Clinic. The research design used is Correlational Analysis with a Cross-Sectional approach. Independent variables are factors that influence the choice of implant contraception. The dependent variable is the attitude of KB acceptors in dealing with the side effects of implants. The population in this study were all family planning acceptors at Sifa Husada Nganjuk Clinic with a sample of 54 respondents taken using the Cluster Random Sampling technique. Analysis using Chi Square and Spearman Rho with error rate (α = 0.05). The results showed that factor 1) Age value p = 0.808. 2) Education p = 0.403. The conclusion of this study is that there is a relationship between age and education factors with the attitude of family planning acceptors about the side effects of implants at Sifa Husada Nganjuk Clinic.